Enantioselective Synthesis of β‐Amino Acid Derivatives Enabled by Ligand‐Controlled Reversal of Hydrocupration Regiochemistry. (11th September 2020) - Guo, Sheng; Zhu, Jiaqi; Buchwald, Stephen L.
Abstract: A Cu‐catalyzed enantioselective hydroamination of α, β‐unsaturated carbonyl compounds for the synthesis of β‐amino acid derivatives was achieved through ligand‐controlled reversal of the hydrocupration regioselectivity. While the hydrocupration of α, β‐unsaturated carbonyl compounds to form α‐cuprated species has been extensively investigated, we report herein that, in the presence of an appropriate ancillary chiral ligand, the opposite regiochemistry can be observed for cinnamic acid derivatives, leading to the delivery of the copper to the β‐position. This copper can react with an electrophilic aminating reagent, 1, 2‐benzisoxazole, to provide enantioenriched β‐amino acid derivatives, which are important building blocks for the synthesis of natural products and bioactive small molecules. Abstract : The regioselectivity of the hydrocupration of α, β‐unsaturated carbonyl compounds can be reversed in the presence of an appropriate ancillary chiral ligand. This ligand‐controlled reversal of regiochemistry enables enantioselective and β‐selective hydroamination of α, β‐unsaturated carbonyl compounds, with 1, 2‐benzisoxazole as an electrophilic aminating reagent, thereby providing simple and efficient access to N‐unprotected β‐amino acid derivatives.